POTENSI HUTAN WISATA MANGROVE DESSRIMINOSARI KECAMATAN LABUHAN MARINGGAI BERBASIS EKOWISATA UNTUK EKOPEDAGOGI KEPADA MASYARAKAT - Tyas, Desy Prasetyaning; widowati, Hening; Achyani, Achyani (Universitas Muhammadiyah Metro, 2020)
Focus of this research are the potential of mangrove forest tourism in Sriminosari Village Labuhan Maringgai District in terms of diversity of flora and fauna, the ecotourism potential of mangrove tourism forest in Sriminosari Village Labuhan Maringgai District, and the feasibility of information sources made regarding the potential of mangrove tourism in Sriminosari Village Labuhan Maringgai District as ecopedagogy in the community. The type of research used in this research is descriptive qualitative. The results of this study indicate the potential diversity of flora in the area of ​​the tourist forest are as many as 11 species while for the diversity of fauna found as many as 5 species. For the potential of ecotourism with 16 indicators displayed found 12 indicators that are already available in the forest tourism area. Based on the results of the overall validation questionnaire analysis of the three aspects namely aspects of language, design, and material obtained a percentage of 88, 43%, with good qualifications.